EFFECT OF INLET AIR COOLING ON GAS TURBINE PERFORMANCE - Abdul Karim, Z. A. (2008)
The performance of gas turbine is always rated to ISO standard condition of 15oC and relative humidity (RH) of 60%. When the gas turbine is operated at ambient condition of relatively low temperature of 24oC and RH of 60%, there is a potential decrease of power output by about 6.3%, accompanied by a 1.8% drop in thermal efficiency and a 1.8% increase in specific fuel consumption when compared to the performance at ISO standard condition. Operating at high ambient temperature of 35oC and RH 60% when compared to ISO standard conditions, the potential power output of gas turbine decrease by about 13.65%, accompanied by a 4.7% drop in thermal efficiency and a 4.7% increase in specific fuel consumption. Another factor influencing in the power output of a gas turbine is the relative humidity of the ambient air, 10% increases in RH decrease the power output by 0.21%, accompanied by a 0.21% drop in thermal efficiency and a 0.21% increase in specific fuel consumption. The purpose of this paper is to study the effect of cooling inlet air in gas turbine.